2013
DOI: 10.1371/journal.pone.0069979
|View full text |Cite
|
Sign up to set email alerts
|

PIMT Prevents the Apoptosis of Endothelial Cells in Response to Glycated Low Density Lipoproteins and Protective Effects of Grape Seed Procyanidin B2

Abstract: BackgroundThe development of diabetic angiopathy is associated with profound vascular endothelial cells (VEC) dysfunction and apoptosis. Glycated low density lipoproteins (gly-LDL) continuously produced in the setting of diabetic patients play an important role in causing VEC dysfunction and apoptosis. However, the underlying molecular mechanism remains largely elusive. Protein L-isoaspartyl methyltransferase (PIMT) is a widely expressed protein repair enzyme by multiple cell types of arterial wall including V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Tumor suppressor gene p53 plays an important role in protection against atherosclerosis and restenosis [30] . Its expression was found negatively correlated with cell proliferation in human atherosclerosis [31] , but directly associated with increased apoptosis [32] , [33] . With regard to H 2 S, many studies have been suggested that H 2 S up-regulated p53 expression to activate cell apoptosis and inhibit cell growth [34] , [35] , [36] .…”
Section: Discussionmentioning
confidence: 92%
“…Tumor suppressor gene p53 plays an important role in protection against atherosclerosis and restenosis [30] . Its expression was found negatively correlated with cell proliferation in human atherosclerosis [31] , but directly associated with increased apoptosis [32] , [33] . With regard to H 2 S, many studies have been suggested that H 2 S up-regulated p53 expression to activate cell apoptosis and inhibit cell growth [34] , [35] , [36] .…”
Section: Discussionmentioning
confidence: 92%
“…Specific polyphenol compounds found in grapes, including quercetin, procyanidin B2, resveratrol and epicatechin are bioactive, and can regulate apoptotic, oxidative stress and inflammatory pathways [23]. Molecular targets of grape-derived compounds include key pro-survival molecules, such as glycogen synthase kinase 3β (GSK3β) [24] and the transcription factor STAT3 [25], among many others. Interestingly, modulating both GSK3β and STAT3 has been shown to improve photoreceptor survival [26].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in ECs using the electronegative LDL subfraction L5 isolated from T2DM patients [ 98 ]. Li et al showed that gLDLs decrease EC survival in a dose-dependent manner by promoting apoptosis [ 99 ]. The authors demonstrated that gLDLs increase p53 nuclear transcription factor levels and activate the glycogen synthase kinase 3 (GSK3b), determining the increase of the cytochrome c release from the mitochondria, which in turn successively activates caspase-9 and the effector caspase-3.…”
Section: Glycated Lipoproteins Detrimental Actions In Endothelial mentioning
confidence: 99%